What Are the Research Avenues for The Analysis of The Relationship Between Capital Structure and Social Responsibility? - Elisabete S. VIEIRA; Mara MADALENO (Communications of International Proceedings, 2024)
This study aims to provide some suggestions for future research on the relationship between capital structure and corporate social responsibility (CSR). To do so, we need to assess the current state of research, know the most recent advancements in this field of research, identify the research gaps, and suggest prospects for future studies. Consequently, we started to develop a bibliometric analysis, using 50 papers that were gathered from the Scopus database between 2010 and 2023. As far as we know, this is the first study to use this method to examine the relationship between capital structure and CSR. This report has implications for corporations, regulators, and other stakeholders. It also affects policymakers, encouraging them to adopt better sustainable practices to enable development towards sustainability. Following the identification of research gaps, it proposes new avenues for future investigation.
Keywords: Capital Structure; CSR; Sustainability; Literature Assessment